FORMATION OF CIVIC IDENTITY AMONG YOUTH IN THE EDUCATIONAL SPACE - Turkboyev , Javohir (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
The article analyzes the formation of civic identity among youth within the contemporary educational space of the Republic of Uzbekistan. It examines theoretical approaches to civic identity, the influence of state policy and educational reforms, the role of schools and higher education institutions, and the impact of digital media and extracurricular activities. Based on analysis of legislation and recent studies, practical recommendations for educational institutions are proposed to foster civic engagement and identity among students.